Gender Diversity in the Executive Board : Draft Report of the Executive Board to the Board of Governors. (Policy Papers; Policy Paper, 2016)
The Report reflects discussion among Executive Directors on June 7, 2016 and responds to the April 16, 2016 Communique of the Thirty-Third Meeting of the IMFC which stated that 'We reiterate the importance of maintaining the high quality and improving the regional, gender, and education diversity of the IMF's staff, and of promoting gender diversity in the Executive Board.'.